2017
DOI: 10.1007/s10935-017-0491-6
|View full text |Cite
|
Sign up to set email alerts
|

And She’s Buying a Stairway to Health: Signs and Participant Factors Influencing Stair Ascent at a Public Airport

Abstract: Several studies have demonstrated that point-of-choice prompts modestly increase stair use (i.e., incidental physical activity) in many public places, but evidence of effectiveness in airport settings is weak. Furthermore, evaluating the effects of past physical activity on stair use and on point-of-choice prompts to increase stair use is lacking. The purpose of this study was to evaluate the influence of sign prompts and participant factors including past physical activity on stair ascent in an airport settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…In our study, when stair use was compared with escalator use, point-of-choice prompts increased stair use by 115 percent, confirming previous findings [4,12], including our own [13], that prompts are an effective means of changing stair-use behavior. However, to more accurately assess the impact on physical activity, we also compared active ascent (stair use or escalator climbing) with passive ascent (escalator standing) and found prompts increased active ascent by only 15 percent.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, when stair use was compared with escalator use, point-of-choice prompts increased stair use by 115 percent, confirming previous findings [4,12], including our own [13], that prompts are an effective means of changing stair-use behavior. However, to more accurately assess the impact on physical activity, we also compared active ascent (stair use or escalator climbing) with passive ascent (escalator standing) and found prompts increased active ascent by only 15 percent.…”
Section: Discussionsupporting
confidence: 89%
“…However, in the studies that reported data on the general population, children and persons with children, disabled persons, persons with luggage and, in online studies, persons under the age of 18 were excluded. Most studies were conducted in the UK [77, 81, 8489, 92, 95, 105], followed by online studies mostly without geographical focus [101104, 106108], and studies from the USA [76, 78, 79, 97, 98, 109], and Hong Kong [75, 80]. There was one study each from Singapore [96], Japan [91], Denmark [83], Sweden [82], Germany [90], Belgium [100], France [99], South Africa [93], and Spain [94].…”
Section: Resultsmentioning
confidence: 99%
“…There was one study each from Singapore [96], Japan [91], Denmark [83], Sweden [82], Germany [90], Belgium [100], France [99], South Africa [93], and Spain [94]. Most studies were conducted in train stations/underground train stations [78, 79, 8183, 8992, 94, 96, 99, 100], followed by studies in malls/shopping malls [7678, 8488, 95, 100], airports [79, 97, 98, 109], pedestrian transit systems [80, 82], two public buildings [79, 93], and one bus station [78]. Eight studies were conducted online only [101108].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous further typical small-scale studies on stair promotion signs have been published. These include stair signs in university settings (Crozier et al, 2019;Engelen 2017;Ly et al, 2019), metro stations (Allias et al, 2017), an airport (Bellettiere et al, 2017), and a city centre office building (Bennett et al, 2018). These studies have continued to reinforce that the magnitude of change in stair use following the installation of a sign is broadly consistent with what has been reported in previous studies.…”
Section: Text Boxmentioning
confidence: 99%